Theta oscillation synchronize VTA and mPFC during ethanol-induced conditioned place preference and stress-evoked anxiety - Yulong Shi; Jie Lei; Chi Cui; Yibo Yao; Kun Ren; Gangan Luo; Xueke Yang; Xiang Peng; Ming Li; Jian Yang; Tongxia Li; Sitong Chen; et al. (Translational Psychiatry)
Summary Addiction and anxiety are two prevalent psychiatric conditions characterized by complex neurobiological mechanisms. It is supported by theta-range (4–12 Hz) neural oscillations that coordinate distant brain regions, such as ventral tegmental area (VTA) and medial prefrontal cortex (mPFC). However, the systematic investigation comparing the analogous and distinct mechanisms of theta oscillations in the mPFC and VTA across these two psychiatric disorders is still needed. Here, we investigate the theta-range (4–12 Hz) local field potential (LFP) signals of the mPFC and VTA in the ethanol-induced conditioned place preference (CPP) and emotional stress-related anxiety-like behavior animal models. We found that the theta oscillation exhibits a significant correlation between the mPFC and VTA in both the two models of male mice. Granger causality suggests that the VTA clearly drives the mPFC in theta band. Our findings suggest potential parallels between the mechanisms of addiction and anxiety, as indicated by the observed theta changes. Further investigation into the mechanisms underlying these changes and their functional impact is necessary to substantiate this link.